2022
DOI: 10.1158/1940-6207.capr-21-0533
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Baseline C-Reactive Protein and the Risk of Lung Cancer: A Prospective Population-Based Cohort Study

Abstract: C-reactive protein (CRP), a systemic marker of diagnosing chronic inflammation, has been associated with the incidence of multiple types of cancer. However, little is known about the impact of CRP on lung cancer incidence in Chinese population. A total of 97,950 participants without cancer at baseline (2006-2007) of the Kailuan Cohort Study were followed up. The concentration of plasma high-sensitivity CRP (hsCRP) was tested for all participants at baseline interview. Multivariable Cox proportional hazards reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Our study was conducted in predominantly never-smokers and light-smokers and our observed inverse DEE-CRP association is consistent with some previous evidence linking lower CRP levels to increased lung cancer risk among never-smokers 8 34. Previous prospective cohort studies have suggested effect modification of CRP-lung cancer associations by smoking status, histological subtype and potentially sex 8 34–38. The seminal meta-analysis in the Lung Cancer Cohort Consortium found positive associations between CRP and lung cancer risk among former smokers and current smokers, and inverse associations among never-smokers 34.…”
Section: Discussionsupporting
confidence: 91%
“…Our study was conducted in predominantly never-smokers and light-smokers and our observed inverse DEE-CRP association is consistent with some previous evidence linking lower CRP levels to increased lung cancer risk among never-smokers 8 34. Previous prospective cohort studies have suggested effect modification of CRP-lung cancer associations by smoking status, histological subtype and potentially sex 8 34–38. The seminal meta-analysis in the Lung Cancer Cohort Consortium found positive associations between CRP and lung cancer risk among former smokers and current smokers, and inverse associations among never-smokers 34.…”
Section: Discussionsupporting
confidence: 91%